Leaders Inspiring the Next Generation of Citizen Scientists – An Analysis of the Predictors of Leadership in Birding - Randler, Christoph (Frontiers in Ecology and Evolution, 2021)
Citizen Science (CS) is a megatrend of the 21st century given its importance for nature conservation. CS projects dealing with bird often require knowledge and abilities to identify species. This knowledge is not easy to acquire and people often learn from leaders during field trips and lectures about birds. This emphasizes the need for leaders in ornithology. Although data of CS projects are increasing, less is known about people providing guidance and taking over leadership roles. In this study, leadership roles (leading field trips, giving lectures/presentations) are analyzed by studying demographic variables, birding specialization and the social dimension of the involvement concept of serious leisure. Participants were recruited via many channels to cover a broad range of birdwatchers in Germany, Austria and Switzerland and participated in the online survey. A total of 1518 participants were men, 1390 were women (mean age 47.7). Mean years of birding were on average 24.5. 845 persons lead at least one field trip, and 671 gave on lecture (in combination 991). Mean number of field trips led during the last five years was 13.43, mean number of presentations was 8.21. Persons that giving presentations also led field trips (Phi = 0.593, p<0.001). However, there are still people that preferred leading field trips but not giving presentations and vice versa. Men more than women took over leadership roles. A binary logistic regression showed an influence of age, gender, and university degree. Social relatedness was related to being a leader, also birding skill/competence as well as self-report behavior of birding were significant predictors for leadership roles. Years of birdwatching and both commitment scales were not significant. The data indicate that more diversity in leadership roles might be beneficial with more women and youngers person.